2022
DOI: 10.3390/pr10071230
|View full text |Cite
|
Sign up to set email alerts
|

A CFD Investigation on the Aerosol Drug Delivery in the Mouth–Throat Airway Using a Pressurized Metered-Dose Inhaler Device

Abstract: Inhalation therapy involving a pressurized metered-dose inhaler (pMDI) is one of the most commonly used and effective treatment methods for patients with asthma. The purpose of this study was to develop a computational fluid dynamics (CFD) model to characterize aerosol flow issued from a pMDI into a simulated mouth–throat geometry. The effects of air flow rate and cone angle were analyzed in detail. The behaviour of the multiphase flow initiated at the inhaler actuation nozzle and extended through the mouth–th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…For the IP, Figure 4A shows the CFD‐predicted contours coloured as a function of air velocity for case I (i.e., injection of particles from the pMDI). As the airflow approaches the 90° bend, centrifugal forces alter the velocity profile, shifting it towards the outer wall of the bend, as reported by Dastoorian et al [ 19 ] In other words, within the elbow, the maximum velocity transitions from the inner wall to the outer wall of the IP. Furthermore, low velocity zones are observed both in the bend on the external wall and downstream of the bend in the vicinity of the inner surface.…”
Section: Resultsmentioning
confidence: 74%
See 2 more Smart Citations
“…For the IP, Figure 4A shows the CFD‐predicted contours coloured as a function of air velocity for case I (i.e., injection of particles from the pMDI). As the airflow approaches the 90° bend, centrifugal forces alter the velocity profile, shifting it towards the outer wall of the bend, as reported by Dastoorian et al [ 19 ] In other words, within the elbow, the maximum velocity transitions from the inner wall to the outer wall of the IP. Furthermore, low velocity zones are observed both in the bend on the external wall and downstream of the bend in the vicinity of the inner surface.…”
Section: Resultsmentioning
confidence: 74%
“…The escape fraction curves determined by Equation (19) for both the IP and the VHC can be utilized for calculating the particle size distribution (PSD) deposited in the NGI stages. For case I, the PSD in the NGI stages is obtained by multiplying the PSD emitted from the pMDI by the deposition fraction function of the IP (see Figure 2A).…”
Section: Comparison Of Experimental and Calculated Deposition Results...mentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, these simulations contribute to the evaluation of inhaler device designs, leading to the development of more efficient and patient-friendly delivery systems. For example, Dastoorian et al [ 177 ] conducted a CFD study to investigate the influence of flow rates and cone angles on spray plume characteristics and drug particle deposition in a simulated mouth-throat airway. They validated their CFD model using experimental data.…”
Section: Model Validationmentioning
confidence: 99%
“…However, their study showed no correlations between aerosol performance/plume angles/ nozzle design with aerosol deposition. Dastoorian et al (2022) studied the effect of plume angle on drug deposition and found that smaller cone angles produced larger particles, but larger cone angles increased mouth deposition. Duke et al (2021b) discovered that pMDI actuators with twin-hole orifices with smaller diameter holes (0.22 mm) could produce up to 75% more FPF compared to the conventional single-hole orifices.…”
Section: Introductionmentioning
confidence: 99%